If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -2m + 3x + 4m = 0 Reorder the terms: -2m + 4m + 5x + 3x = 0 Combine like terms: -2m + 4m = 2m 2m + 5x + 3x = 0 Combine like terms: 5x + 3x = 8x 2m + 8x = 0 Solving 2m + 8x = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-8x' to each side of the equation. 2m + 8x + -8x = 0 + -8x Combine like terms: 8x + -8x = 0 2m + 0 = 0 + -8x 2m = 0 + -8x Remove the zero: 2m = -8x Divide each side by '2'. m = -4x Simplifying m = -4x
| -4x^2+60x+900=0 | | 1/19+m=1/19 | | x^2+5x-80=0 | | -(-4-3n)= | | 8y+3=44 | | 2x=6+6 | | 2x+17=5x+8 | | -6.5=p+2.1 | | 0.25-0.4=0.15y+1-0.6y | | 10=.28571j+4 | | 7/2+1 | | 250/0.1 | | -1/2(8x+4)+1/9(54x+45)= | | -1/2x+3/7=5/7 | | -3/2-(-2+n)=-5+5n/2 | | 50m+100=100m+50 | | 1/2*3.14 | | 3h-2h+3h+m+2m= | | (2x^3)-18x+1=0 | | x^4-4x^2+14=0 | | 5*1/2+1 | | 6n-4=-22+3n | | 1/2(6x+10)+2=-20 | | -1/2+3/7=5/7 | | 3+x=31/8 | | 4x-34=-4x+14 | | 5-(t-3)=-1+2(t+3) | | -1x-7=5x-19 | | 3n+3=50 | | (-3x/2)=3-x | | 4y+5x+3x-2y= | | 8(8x+4)=80 |